Comparative study on the ability of IgG and Fab sheep antivenoms to neutralize local hemorrhage, edema and myonecrosis induced by Bothrops asper (terciopelo) snake venom - León Montero, Guillermo (2000)
The ability of sheep antivenoms, consisting of whole IgG molecules or Fab fragments, to neutralize local hemorrhage, edema and myonecrosis induced by Bothrops asper venom was comparatively studied in mice. The two antivenoms were produced from the same batch of hyperimmune plasma and were adjusted to the same neutralizing potency against these effects in assays where venom and antivenoms were incubated prior to injection. Thus, if differences are observed in experiments involving independent injection of venom and antivenoms, they would depend on the pharmacokinetic profiles of the products. Despite the observation that both antivenoms neutralized the three effects if preincubated with venom, neutralization was only partial when antivenoms were administered i.v. at various time intervals after envenomation. No significant differences were observed between IgG and Fab antivenoms concerning neutralization of hemorrhagic and edema-forming activities, whereas IgG antivenom was slightly more effective in neutralizing myotoxic activity in experiments involving independent injection of venom and antivenom. These results do not support the hypothesis that Fab fragments are more effective than whole IgG molecules in the neutralization of locally-acting toxins from B. asper venom.